Desorden esquelético con malformaciones faciales en cerámico de la cultura Moche - Purizaca-Rosillo, Nelson (2020)
Moche is a culture that developed between 200 y 850 AD in the Peruvian northern coast. Their pottery artefacts were crafted showing many details, they were very realistic, and different physical malformations have been identified in these pieces. We present the case of the piece C-00122 that is kept in the Natural and Cultural History Museum of Universidad Privada Antenor Orrego (NCHM-UPAO), which shows a skeletal disorder associated to some facial malformations. We discuss the case and propose different likely diagnoses.